Study of Physical Chemistry of Rice Analog Baruk Agostarch Heat Moisture Treatment (HMT) With The Addition of Flour Composites - Sede, Viviyanti J.; Mamuaja, Christine F.; Djarkasi, Gregoria S. S. (Jurnal Ilmu dan Teknologi Pangan, 2015)
Sago baruk (Arenga microcarpa) is one food that can be eaten as a source of carbohydrate. This study aims to get the right formulation and the best analogue for the manufacture of composite flour rice that consumers preferred, analyzing physical chemistry rice flour composite analog and analog getting rice starch which has resiten and increase its nutritional value. The research begins with manufacture baruk sago starch, sago starch manufacture baruk modification Heat Moisture treatments (HMT), the manufacture of flour and flour-making bulbs purse red beans and rice manufacture analog. The experimental design used was completely randomized design (CRD) with 7 (seven) treated with 3 (three) replications with a ratio of P1: 100% Starch Sago Natural (control), P2: 100% Starch Sago modification HMT, P3: 90% Starch Sago Modification HMT + 5% Wheat Bulbs purse + 5% Flour Red Beans, P4: 80% starch Sago Modification HMT + 10% Wheat Bulbs purse + 10% Flour Red Beans, P5: 70% starch Sago Modification HMT + 15% Flour Bulbs purse + 15% Flour Red Beans, P6: 60% Starch Sago Modification HMT + 20% Flour tubers purse + 20% Flour Red Beans, P7: 50% Starch Sago Modification HMT + 25% Flour tubers purse + 25% Flour Red Beans . To get the exact formula and favored by consumers, the comparison is done organoleptic test for flavor, aroma, color and texture then performed physical analysis of texture, color test, gelatinization temperature, density Kamba, weight of 100 grains, whereas the chemical analysis, namely: Level of water ash, protein content, fat content, starch, amylose, amylopectin and starch digestibility in vitro against most favored treatment. Â The results show thatthe most preferred formula is P6 which is the ratio: 60% Sago Starch Modified Starch HMT + 20% + 20% Bulbs purse Red Bean Flour. Physical analysis ie texture: 2 mm / g.det, Kamba density of 0.497 g / ml, weight of 100 grains: 4.480 g, Test color L * 36.56, a * 8.56 b * 16.22, gelatinization temperature of 65 OC with a time of 31 minutes. Sedangakn Chemical analysis results are: 14.10% moisture content, ash content of 0.93%, 5.83% protein content, fat content 0.2%, 73% starch content, amylose 20.66%, 52.34% amylopectin , and in vitro starch digestibility 8.68%. Keywords : analog rice, sago baruk, starch